Secondary batteries and electrical devices
By regulating the potential difference and lithium ion diffusion coefficient of lithium ion batteries under 2C charging conditions, the problem of rapid change in potential of lithium ion batteries during fast charging is solved, and higher fast charging efficiency and longer cycle life are achieved.
Patent Information
- Application Number
- CN202411641272.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-11-18
AI Technical Summary
During the fast charging process of existing lithium-ion batteries, the rapid rise of the positive electrode potential leads to a rapid decline in the negative electrode potential, shortening the large-scale charging stage, affecting the charging efficiency and overall charging time of the battery.
By controlling the potential difference (U) of the two charging platforms with low SOCs under the 2C charging conditions of the secondary battery and the lithium ion diffusion coefficient (r) corresponding to the negative electrode sheet when the battery potential is in the first platform, to ensure 0.06≤U×r≤0.189, the fast charging performance of the battery is optimized.
It achieves the shortening of the battery charging time, improves the fast charging cycle life, and improves the fast charging capability of the secondary battery.
Smart Images

Figure CN119153825B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrochemical technology, in particular to a secondary battery and an electrical device. Background Art
[0002] Lithium-ion batteries are widely used in many fields such as 3C electronic products, power vehicles and energy storage power stations due to their high energy density, low self-discharge, no memory effect and long cycle life. They are currently a research hotspot in new energy storage and conversion systems.
[0003] The positive electrode material has a great impact on the performance and cost of the battery. Among them, the olivine-structured lithium manganese iron phosphate, adhering to the olivine structure of phosphate materials, has the same safety performance as lithium iron phosphate. In addition, the addition of manganese elements also greatly improves the reaction potential of lithium iron phosphate. Therefore, in recent years, lithium manganese iron phosphate (LMFP) has an increasingly higher market share in the power battery market.
[0004] However, during the use of the battery, the LMFP positive electrode material shows some limitations in the fast charging process. In the early stage of charging, the potential of the positive electrode is high, and during the high-rate charging process, the rapid rise of the positive electrode potential further pulls the rapid drop of the negative electrode potential. This rapid change in potential leads to a significant shortening of the high-rate charging stage, which is not conducive to the charging efficiency of the battery and prolongs the overall charging time of the battery.
[0005] Therefore, it is necessary to develop a secondary battery with higher fast charging capability. Summary of the invention
[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a secondary battery and an electrical device. By comprehensively regulating the potential difference between the two charging platforms of the secondary battery with a low SOC under 2C charging conditions and the lithium ion diffusion coefficient of the negative electrode plate corresponding to the battery potential when the battery potential is at the first platform, the charging time of the battery is shortened, the fast charging cycle life is improved, and the secondary battery has excellent fast charging capability.
[0007] To achieve the above object, in a first aspect of the present invention, the present invention provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material, and the positive electrode active material comprises a phosphate material;
[0008] The secondary battery is charged at 25°C at a 2C rate in a voltage range of 2.5-4.25V to obtain a charging curve, which includes three charging platforms with different potentials, which are recorded as the first platform, the second platform and the third platform in order from low to high potential. The potential difference between the first platform and the second platform is recorded as U, and the unit of measurement is V.
[0009] When the potential of the secondary battery is at the first platform, the lithium ion diffusion coefficient of the corresponding negative electrode is r, and the unit of measurement is: ×10 -8 cm 2 / s;
[0010] The secondary battery satisfies the following relationship: 0.06≤U×r≤0.189.
[0011] As a preferred embodiment of the present invention, the secondary battery satisfies the following relationship: 0.124≤U×r≤0.152.
[0012] As a preferred embodiment of the present invention, the range of U is 0.07~0.19V.
[0013] As a further preferred embodiment of the present invention, the range of U is 0.13~0.16V.
[0014] As a preferred embodiment of the present invention, the range of r is 0.7×10 -8 ~1.28 × 10 -8 cm 2 / s.
[0015] As a further preferred embodiment of the present invention, the range of r is 0.9×10 -8 ~1.05×10 -8 cm 2 / s.
[0016] As a preferred embodiment of the present invention, the phosphate material includes lithium manganese iron phosphate and lithium iron phosphate.
[0017] As a preferred embodiment of the present invention, the Dn50 particle size of the lithium iron phosphate is 0.6-1.5 μm.
[0018] As a preferred embodiment of the present invention, the Dn50 particle size of the lithium manganese iron phosphate is 60~200nm.
[0019] As a preferred embodiment of the present invention, the mass ratio of the lithium manganese iron phosphate to the lithium iron phosphate is (1.5-19):1.
[0020] As a further preferred embodiment of the present invention, the mass ratio of the lithium manganese iron phosphate to the lithium iron phosphate is (2-6):1.
[0021] As a preferred embodiment of the present invention, the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer arranged on at least one surface of the negative electrode current collector, the negative electrode active material layer contains negative electrode active material, and the negative electrode active material includes at least one of natural graphite, artificial graphite, mesophase carbon microbeads, hard carbon, soft carbon, silicon, SiOx, silicon carbon, and lithium titanate.
[0022] In a second aspect of the present invention, the present invention provides an electrical device comprising the secondary battery described above.
[0023] The beneficial effects of the present invention are:
[0024] The present invention provides a secondary battery and an electric device. The present invention improves the fast charging performance of the secondary battery, shortens the charging time of the secondary battery, and increases the fast charging cycle life by comprehensively regulating the potential difference between two charging platforms with lower potentials under 2C charging conditions and the lithium ion diffusion coefficient of the negative electrode under specific conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a charging curve diagram of the lithium-ion battery of Example 1.
[0026] Figure 2 dQ / dV-V curve of the lithium ion battery of Example 1. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] In the present invention, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0029] In the present invention, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0030] In the present invention, there is no particular limitation on the specific dispersion and stirring treatment methods.
[0031] The reagents or instruments used in the present invention without indicating the manufacturer are all conventional products that can be obtained through commercial purchase.
[0032] An embodiment of the present invention provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material, and the positive electrode active material comprises a phosphate material;
[0033] The secondary battery is charged at 25°C at a 2C rate in a voltage range of 2.5-4.25V to obtain a charging curve, wherein the charging curve includes three charging platforms with different potentials, which are sequentially recorded as the first platform, the second platform and the third platform in order from low to high potentials; the potential difference between the first platform and the second platform is recorded as U, and the unit of measurement is V.
[0034] When the potential of the secondary battery is at the first platform, the lithium ion diffusion coefficient of the corresponding negative electrode is r, and the unit of measurement is: ×10 -8 cm 2 / s;
[0035] The secondary battery satisfies the following relationship: 0.06≤U×r≤0.189.
[0036] In the fast charging technology of secondary batteries, the charging performance of the battery is closely related to the material properties of the electrode material and the working state of the electrode. The present invention has found that under 2C charging conditions, the comprehensive regulation of the potential difference (U) between the two charging platforms with lower potential of the secondary battery and the lithium ion diffusion coefficient (r) of the negative electrode corresponding to the battery potential at the first platform is the key to improving the fast charging performance of the secondary battery.
[0037] The charging mechanism of fast charging of batteries is to use a high rate of charging at the beginning of charging, and then gradually reduce it until it is fully charged. In the initial charging stage, the negative electrode has the best lithium insertion capacity and can meet the insertion of a large number of lithium ions, so a high rate of charging can be used in the early stage of charging. When the potential difference U is moderate, the polarization of the positive electrode can be improved in the high rate charging stage, and the excessively rapid drop of the negative electrode voltage can be effectively suppressed, thereby ensuring the high rate charging time, reducing the entire charging time, and improving the fast charging performance.
[0038] The lithium ion expansion coefficient r of the negative electrode reflects the lithium insertion capacity of the negative electrode. When U and r satisfy the relationship 0.06≤U×r≤0.189, the fast charging capability of the battery is significantly improved, not only the fast charging rate is relatively higher, but also the cycle life is better under fast charging conditions.
[0039] When U×r exceeds 0.189, the potential difference of the battery at the low potential platform is too large, and the lithium ion diffusion coefficient of the negative electrode is too high; in the early stage of charging, when the remaining battery power is low (that is, low SOC) and the charging rate is high, due to the increase in current density, a large number of lithium ions will accumulate on the surface of the negative electrode, resulting in the obstruction of lithium embedding in the negative electrode body, and the battery's fast charging rate is poor. This lithium ion accumulation not only affects the normal lithium embedding of the negative electrode, but may also cause structural damage to the negative electrode material, thereby affecting the stability and cycle life of the battery. In addition, at high SOC, the positive electrode active material will withstand a greater current density, and the high load will aggravate the polarization of the positive electrode, making it difficult for lithium ions to escape from the positive electrode, thereby extending the fast charging time. This not only leads to a decrease in the charging efficiency of the battery, but may also increase the thermal risk of the battery during high-rate charging, and also reduce the fast charging cycle life of the battery.
[0040] When U×r is lower than 0.06, the potential difference of the battery at the low potential platform is too small to effectively improve the fast charging capability of the battery; the lithium ion diffusion coefficient of the negative electrode of the battery is too low, which may mean that the charge transfer impedance (Rct) of the negative electrode sheet at the first platform potential is too large. The increased impedance limits the diffusion capacity of lithium ions at the negative electrode interface, making it difficult for the negative electrode to effectively embed lithium ions. As a result, at the low SOC in the initial charging stage, the high-rate charging time of the battery is shortened, the overall charging rate of the battery deteriorates, and the charging time is extended.
[0041] Illustratively, in the present invention, the value of U×r may be 0.060, 0.070, 0.080, 0.090, 0.095, 0.100, 0.110, 0.150, 0.180, or 0.189.
[0042] In one embodiment, the secondary battery satisfies the following relationship: 0.124≤U×r≤0.152.
[0043] When U and r are within the above range, the secondary battery has better fast charging capability, its fast charging time is shorter, and its fast charging cycle life is relatively higher.
[0044] For the secondary battery of the present invention, the potential of the first platform is generally 3.4-3.6V, and the potential of the second platform is generally 3.6-3.8V.
[0045] In one embodiment, the range of U is 0.07~0.19V.
[0046] In one preferred embodiment, the range of U is 0.13~0.16V.
[0047] The present invention has found that when U is within an appropriate range, the fast charging capability and cycle performance of the battery are better. When the U value is too large, it means that the potential difference between the first platform and the second platform is too large. When the battery is in a high SOC, fast charging is performed, and the electrode polarization is expanded, which will cause the charging time to be extended. In particular, when the potential value of the second platform is too high, the negative electrode potential will be pulled down rapidly, and the fast charging performance of the battery is poor. In addition, a large U value may indicate that the potential of the first platform is too low. For LMFP batteries, the loss of active lithium at the negative electrode is the main factor in the decay of the cycle capacity, resulting in the decay of the capacity of the low potential platform of the positive electrode at the end of the discharge. The lower the potential of the first platform, the greater the decay risk, and the lower the cycle capacity retention rate of the battery. When the U value is too small, the potential difference between the first platform and the second platform is too small. When the battery is charged at a low SOC, as the positive electrode potential rises, the corresponding negative electrode potential drops rapidly and reaches the cut-off potential, resulting in the battery being in a very short stage of high-rate charging, and the improvement of the fast charging rate of the battery is not obvious.
[0048] The value of U is related to factors such as the type, composition, material morphology and electrochemical properties of the phosphate materials in the positive electrode active material. The value of U can be adjusted by controlling the chemical element composition and ratio of the phosphate materials in the positive electrode active material, as well as the particle morphology, crystal structure, and processing technology.
[0049] In the present invention, the value of U can be obtained from the charging curve of the secondary battery.
[0050] Specifically, U can be measured by the following method:
[0051] (1) Constant capacity: The secondary battery was left at 25°C for 120 min, and then discharged at a constant current of 0.33C to 2.5V. After leaving the battery at 25°C for 20 min, the battery was charged at a constant current of 0.33C to 4.25V, charged at a constant voltage of 0.05C, and discharged at a constant current of 0.33C to 2.5V. The above steps were repeated once to obtain the charge capacity Q0 of the second cycle.
[0052] (2) Draw a charging curve: After standing at 25°C for 120 min, charge at a constant current of 2C to an upper voltage limit of 4.25 V to obtain the charging capacity Q and voltage V data;
[0053] (3) Derivative calculation is performed on the above QV data, and then dQ is divided by dV to obtain dQ / dV; dQ / dV is used as the ordinate and voltage V is used as the abscissa to obtain a dQ / dV-V curve;
[0054] (4) In the dQ / dV-V curve, the peak position of the characteristic peak with a voltage between 3.4 V and 3.6 V on the horizontal axis is the potential U1 of the first platform, and the peak position of the characteristic peak with a voltage between 3.6 V and 3.8 V on the horizontal axis is the potential U2 of the second platform; the potential difference between the first platform and the second platform is U = U2 - U1, in V.
[0055] In one embodiment, the range of r is 0.7×10 -8 ~1.28 × 10 -8 cm 2 / s.
[0056] In one embodiment, the range of r is 0.9×10 -8 ~1.05×10 -8 cm 2 / s.
[0057] During the charging process of lithium-ion batteries, the lithium ion diffusion coefficient (r) of the negative electrode at the first platform potential directly affects the charging efficiency and stability of the battery. The value of r reflects the transmission and embedding speed of lithium ions in the negative electrode of the battery. When r is within the appropriate range, the negative electrode has good lithium ion transmission and embedding and extraction characteristics, and the solid electrolyte membrane (SEI membrane) on the surface of the negative electrode has good stability, and the battery has excellent fast charging rate and fast charging cycle performance. When the r value is too large and exceeds the above preferred range, the transmission of lithium ions in the negative electrode bulk phase is very rapid. At this time, the layered structure of the negative electrode is quickly "opened", exposing a large number of active sites, and it is very easy to cause the SEI membrane to rupture, induce serious interfacial side reactions, and deteriorate high temperature stability. When the r value is large, although the transmission rate of lithium ions in the bulk phase is improved, it is not only the bulk phase but also the interface that limits the insertion of lithium in the negative electrode. Therefore, at this time, the fast charging performance of the battery will not be significantly improved, and when the bulk phase transmission is faster, the exposure of active sites caused by structural expansion will induce interfacial side reactions, which will reduce the risk of interfacial transmission, and the fast charging performance will be reduced. When the r value is too small, lower than the above preferred range, the diffusion rate of lithium ions in the negative electrode is slow, resulting in increased polarization of the negative electrode. The interfacial active lithium has no time to be embedded in the bulk phase, resulting in the risk of lithium precipitation, deterioration of fast charging performance, and prolonged charging time.
[0058] The value of r is affected by many factors such as the negative electrode active material in the negative electrode sheet, the negative electrode sheet design, and the electrolyte. The value of r can be controlled to meet the scope of the technical solution of the present invention by adjusting the type, raw material, processing technology, morphology of the negative electrode active material, and the content of each component in the negative electrode active material layer. In the present invention, the detection method of r is not limited, and those skilled in the art can detect the ion diffusion coefficient of the negative electrode sheet at a specific first platform potential according to conventional technical means, such as electrochemical impedance spectroscopy (EIS) testing.
[0059] Exemplarily, r can be detected by the following method:
[0060] (1) The positive electrode and negative electrode in the secondary battery are disassembled and reassembled into a single battery. The separator used is a PE separator. There is no special restriction on the electrolyte composition. The injection amount is sufficient to ensure that there is free electrolyte when the battery is charged to the upper limit voltage. A copper wire is fixed on the negative electrode side as the third electrode;
[0061] (2) After the single-chip battery is assembled, it is allowed to stand at 25°C for 120 minutes, first charged to 4.25V at a constant current of 0.03C, then discharged to 2.5V at a constant current of 0.3C, then charged to 4.25V at a constant current of 0.33C, then charged to 0.05C at a constant voltage, allowed to stand at 25°C for 10 minutes, and then discharged to 2.5V at a constant current of 0.33C; after repeating twice, the third electrode is plated with lithium using the positive electrode at 0.01C for 6 hours; after the lithium plating is completed, it is charged at 0.33C to the voltage of the first platform; allowed to stand at 25°C for 30 minutes, and the EIS test is continued; the negative electrode and the third electrode are monitored; the test frequency is 0.01 ~10 6 Hz;
[0062] (3) After the test, the EIS data is obtained and the low-frequency oblique line area is taken as ω -0.5 -Z' curve of the real part of impedance, take the slope σ of the straight line in the lowest frequency region; substitute this slope into the formula: DLi + =(R 2 T 2 ) / (2A 2 n 4 F 4 C 2 σ 2 ) to get DLi + It is the lithium ion diffusion coefficient (r); where R is the gas constant J / mol / K, T is the absolute temperature of the reaction K, and A is the area of the negative electrode material immersed in the electrolyte cm 2 , n is the number of reaction electrons, F is the Faraday constant C / mol, and C is the molar concentration of lithium ions mol / cm 3 .
[0063] In one embodiment, the phosphate material includes lithium iron manganese phosphate and lithium iron phosphate.
[0064] The phosphate material in the present invention includes a mixture of lithium iron phosphate (LFP) and lithium manganese iron phosphate (LMFP). LFP and LMFP have different material properties, especially different charge and discharge properties. Reasonable compounding of LFP and LMFP helps the secondary battery of the present invention achieve better fast charging capability.
[0065] In the early stage of fast charging of the battery, the decrease in the negative electrode potential is not only affected by the embedding of lithium ions and its own interface and bulk impedance, but the oxidation reaction of the positive electrode at high potential will further aggravate the decrease in the negative electrode potential. When phosphate materials including LFP and LMFP are blended, the incorporated LFP will take precedence over LMFP for delithiation, forming an oxidation platform with a lower potential, thereby alleviating the decrease in the negative electrode potential and increasing the lithium ion embedding space of the negative electrode. In addition, the positive electrode metal dissolves and deposits at the negative electrode, which catalyzes the formation of the negative electrode SEI film and affects the interfacial impedance of the negative electrode. The present invention has found that an appropriate amount of manganese dissolution from LMFP can reduce the impedance of the negative electrode SEI film. Therefore, the compounding of LFP and LMFP contributes to a better fast charging capability of the secondary battery.
[0066] In one embodiment, the mass ratio of lithium manganese iron phosphate to lithium iron phosphate is (1.5-19):1.
[0067] In one preferred embodiment, the mass ratio of lithium manganese iron phosphate to lithium iron phosphate is (2-6):1.
[0068] Within the above preferred range, the compounding effect of LFP and LMFP is better, the fast charging capability of the secondary battery is improved more significantly, and the improvement effect of the fast charging rate and the fast charging cycle life is more balanced.
[0069] In one embodiment, the Dn50 particle size of the lithium iron phosphate is 90-200 nm.
[0070] In one preferred embodiment, the Dn50 particle size of the lithium iron phosphate is 150-180 nm.
[0071] In one embodiment, the Dn50 particle size of the lithium manganese iron phosphate is 50-180 nm.
[0072] In one embodiment, the Dn50 particle size of the lithium manganese iron phosphate is 90-120 nm.
[0073] The particle size of LFP and LMFP, as the morphological characteristics of the positive electrode active materials, not only affects the size of the U value, but also affects the overall dynamic performance and stability of the battery. The compounding of LFP and LMFP with appropriate particle sizes helps to shorten the transmission path of lithium ions and make the contact area between the positive electrode active material and the electrolyte appropriate, thereby avoiding excessive interfacial side reactions on the basis of improving the battery's dynamic performance. In addition, during repeated charging and discharging, the positive electrode active material particles experience a certain degree of volume expansion and contraction. Especially under fast charging conditions, the internal stress borne by the positive electrode active material is relatively greater. By compounding materials with specific particle sizes, the mechanical stability of the positive electrode active material can be improved, and the fast charging cycle life can be improved.
[0074] The particle size of lithium iron phosphate and lithium iron manganese phosphate can be controlled by adjusting the raw material selection and preparation process of lithium iron phosphate and lithium iron manganese phosphate.
[0075] In the present invention, the present invention does not limit the testing method of the particle size of lithium iron phosphate and lithium iron manganese phosphate, and those skilled in the art can detect the particle size of lithium iron phosphate and lithium iron manganese phosphate according to conventional technical means.
[0076] For example, the particle size of lithium iron phosphate and lithium iron manganese phosphate can be detected by the following method:
[0077] Take an empty positive electrode sheet and soak it in a dimethyl carbonate (DMC) solution at room temperature for 4 hours. After soaking, take out the positive electrode sheet and dry it in a vacuum environment, and use a ceramic knife to scrape the positive electrode active material powder on the surface of the positive electrode sheet;
[0078] The scraped positive electrode active material powder was evenly dispersed in ethanol and tested by SEM (scanning electron microscope). In the SEM observation field, the elements were collected by EDS (energy dispersive X-ray spectroscopy) point scanning to confirm the lithium iron phosphate particles and lithium manganese iron phosphate particles;
[0079] The size of lithium iron phosphate particles and lithium iron manganese phosphate particles was measured on the SEM images using the MEARSURE NANO software. The particle size was collected using the diagonal streak method. After the sample size reached more than 100, the particle size distribution was statistically analyzed, and the Dn50 particle size of lithium iron phosphate and lithium iron manganese phosphate was calculated. Dn50 is the particle size corresponding to when the cumulative number of particles in the number base distribution reaches 50%.
[0080] In the present invention, the preparation method of LMFP is not limited, and those skilled in the art can prepare LMFP according to conventional technical means.
[0081] Exemplarily, the preparation method of LMFP may include the following steps:
[0082] A manganese source, an iron source, a phosphorus source, a lithium source and a carbon source (if any) are mixed in a certain molar ratio, dispersed in a solvent, reacted, and obtained a mixed solution;
[0083] The mixed solution is spray-dried to obtain a powder;
[0084] The spray-dried powder is sintered in an atmosphere with an oxygen concentration of less than 150 ppm;
[0085] The sintered material is crushed and screened to obtain LMFP.
[0086] Specifically, the preparation method of LMFP may include the following steps:
[0087] A manganese source, an iron source, a phosphorus source, and a lithium source are mixed in a certain molar ratio and dispersed in deionized water, and the reaction ion concentration is controlled to be 1-8 M; a carbon source is then added to react to obtain a mixed solution;
[0088] The mixed solution is spray-dried to obtain a powder;
[0089] The spray-dried powder is sintered in an atmosphere with an oxygen concentration of less than 150 ppm;
[0090] The sintered material is crushed and screened to obtain LMFP.
[0091] Exemplarily, the preparation method of LFP may include the following steps:
[0092] Mixing an iron source, a phosphorus source, a lithium source and a carbon source (if any) in a certain molar ratio, and performing sand milling of the mixed material;
[0093] The mixed material is sand-milled and sintered in an atmosphere with an oxygen concentration of less than 150 ppm;
[0094] The sintered material is crushed and screened to obtain LFP.
[0095] Optionally, in the preparation method of LFP, after the sintering step, a step of sand grinding the finished product may be added as needed.
[0096] Specifically, the preparation method of LFP may include the following steps:
[0097] The iron source, phosphorus source, lithium source and carbon source (if any) are mixed in a certain molar ratio and sand-milled; the linear speed of the sand-milling is 3-10 m / s and the time is 2-7 hours;
[0098] The sand-milled product is sintered in an atmosphere with an oxygen concentration of less than 150 ppm;
[0099] The mixed material is sand-milled and sintered in an atmosphere with an oxygen concentration of less than 150 ppm;
[0100] The sintered material is subjected to finished product sand grinding, the line speed of the finished product sand grinding is 8-15 m / s, and the time is 2-6 hours;
[0101] The finished product after sand grinding is crushed and then screened to obtain LFP.
[0102] The lithium source may include at least one of lithium hydroxide, lithium carbonate, lithium nitrate, lithium oxalate, lithium dihydrogen phosphate, lithium citrate or lithium acetate.
[0103] The phosphorus source may include at least one of diammonium hydrogen phosphate, lithium dihydrogen phosphate, ammonium phosphate, or lithium phosphate.
[0104] The iron source may include at least one of ferrous oxalate, ferric hydroxide, ferrous hydroxide, ferric phosphate, ferrous phosphate, ferric acetate, ferrous acetate, ferric carbonate, ferrous carbonate, ferrous oxide, ferrous oxide or ferric oxalate.
[0105] The manganese source may include at least one of manganese carbonate, manganese sulfate, manganese nitrate, manganese chloride, manganese oxalate, or manganese acetate.
[0106] The carbon source may include glucose and / or sucrose.
[0107] Ferromanganese phosphate can be selected as a manganese source, an iron source and a phosphorus source at the same time; ferric phosphate can be selected as a manganese source, an iron source and a phosphorus source at the same time; the lithium source can include at least one of lithium hydroxide, lithium carbonate, lithium nitrate, lithium oxalate, lithium dihydrogen phosphate, lithium citrate or lithium acetate.
[0108] When preparing LMFP and / or LFP, a certain amount of doping element source such as vanadium source (vanadium pentoxide), tungsten source (ammonium metatungstate), titanium source (titanium oxide), magnesium source (magnesium carbonate), etc. can be mixed with manganese source (if any), iron source, phosphorus source, lithium source, etc. as needed to obtain LMFP and / or LFP containing a certain amount of doping elements.
[0109] By adjusting the addition amount of manganese source, iron source and phosphoric acid, the proportion of manganese content in LMFP can be controlled.
[0110] The particle size of LMFP or LFP can be controlled by adjusting the amount and type of carbon source added, ball milling conditions, sintering conditions, or by changing crushing conditions and controlling screening conditions.
[0111] In addition to the above-mentioned positive electrode active material, the positive electrode active material layer may further include a conductive agent and a binder.
[0112] The conductive agent can be used as long as it has suitable electronic conductivity and does not cause adverse chemical changes in the battery. In the present invention, there is no particular limitation on the type of the conductive agent. Specifically, the conductive agent can be at least one of carbon nanotubes, carbon black or graphene.
[0113] The binder is used to improve the adhesion between the positive electrode active material particles and the adhesion between the positive electrode active material and the current collector. In the present invention, the binder can be a conventional choice in the battery field. Specifically, the conductive agent can be at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl alcohol (PVA), styrene-butadiene rubber (SBR), polyacrylonitrile (PAN), polyimide (PI), polyacrylic acid (PAA), polyacrylate, polyolefin, sodium carboxymethyl cellulose (CMC) or sodium alginate.
[0114] The present invention has no particular limitation on the positive electrode current collector as long as it has conductivity and does not cause adverse chemical changes in the battery, and can use, for example: stainless steel, aluminum, nickel, titanium, fired carbon; or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc.
[0115] In the present invention, the positive electrode sheet can be prepared according to conventional methods in the art, for example, the positive electrode active material, the conductive agent and the binder are dispersed in a solvent to form a uniform positive electrode slurry, the positive electrode slurry is coated on the positive electrode collector, and after drying, rolling and other processes, the positive electrode sheet is obtained.
[0116] In one embodiment, the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, the negative electrode active material layer contains a negative electrode active material, and the negative electrode active material includes at least one of natural graphite, artificial graphite, mesophase carbon microbeads, hard carbon, soft carbon, silicon, SiOx, silicon carbon, and lithium titanate.
[0117] The diaphragm is located between the positive electrode sheet and the negative electrode sheet, and is used to separate the positive electrode sheet and the negative electrode sheet to prevent the positive electrode sheet and the negative electrode sheet from contacting and short-circuiting. The diaphragm can be any material suitable for an electrochemical energy storage device isolation membrane in the art. Specifically, the diaphragm includes at least one of polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester, and natural fiber.
[0118] The electrolyte of the present invention can be any electrolyte suitable for electrochemical energy storage devices in the art. The electrolyte includes an electrolyte and a solvent, and the electrolyte can generally include a lithium salt.
[0119] Specifically, the lithium salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP). The concentration of the electrolyte in the electrolyte may be 0.5-5 mol / L.
[0120] Specifically, the solvent includes at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0121] An embodiment of the present invention provides an electric device, comprising the secondary battery described above.
[0122] The electrical device serves as a power supply for the electrical device.
[0123] The electrical device refers to any device that can utilize electrical energy and convert it into mechanical energy, thermal energy, light energy or other energy forms, such as electric motors, electric heat engines, electric light sources, etc. Specifically, it may include but is not limited to mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc. Mobile devices may be mobile phones, laptops, drones, sweeping robots, electronic cigarettes, etc.; electric vehicles may be pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.
[0124] The present invention is further described below with reference to specific embodiments.
[0125] Example 1
[0126] Embodiment 1 provides a lithium ion battery, and the preparation method is as follows:
[0127] (1) Preparation of positive electrode
[0128] (1.1) Preparation of positive electrode active materials
[0129] Preparation of LMFP: According to LiMn a Fe b The molar ratio of Li, Mn, Fe, and P in the PO4 chemical formula (a / b value is 72 / 25) is respectively weighed. Lithium hydroxide, manganese sulfate, ferric chloride, and potassium dihydrogen phosphate are added to deionized water and stirred until completely dissolved. The amount of deionized water is adjusted to control the reaction ion concentration to 1.5M, and then the temperature is raised to 65°C and kept warm for 3 hours. The pH value is 7 to obtain the reaction precursor. Then according to the reaction product LiMn a Fe b 20wt.% of the total weight of PO4 was weighed glucose, added to the above solution, and continued to stir and disperse at a dispersion speed of 500rpm for 2h. The mixed solution was spray dried to obtain dry powder, and the dry powder was sintered under a protective atmosphere. The tubular furnace was heated from room temperature to 400℃ at a uniform rate of 5℃ / min, and then kept warm for 5h, and then continued to heat to 600℃. After keeping warm for 3h, it was cooled to room temperature by itself. After graded screening, LMFP with a particle size Dn50 of 122nm was obtained, that is, the final product LMFP was obtained.
[0130] Preparation of LFP: According to the molar ratio of Li, Fe, and P elements of 1:1:1, the required ferrous oxalate, diammonium hydrogen phosphate, and lithium carbonate are weighed and mixed by sand milling. At the same time, sucrose is weighed according to 10wt.% of the weight of the LFP product, and the above materials are added for mixed sand milling. The linear speed of the mixed sand milling is 7m / s and the time is 5h; the sand milled materials are sintered in a protective atmosphere, and the tubular furnace is heated from room temperature to 250℃ at a uniform speed of 5℃ / min. After being kept warm for 2h, the temperature is continued to be raised to 700℃ on the sintering platform. After being kept warm on the sintering platform for 6h, it is cooled to room temperature by itself. The obtained materials are sand milled for finished products. The linear speed of the finished product sand milling is 10m / s and the time is 4h. After classification and screening, LMFP with a particle size Dn50 of 320nm is obtained, that is, the final product LFP is obtained.
[0131] (1.2) mixing LMFP and LFP in a mass ratio of 2.6:1 to obtain a positive electrode active material;
[0132] The positive electrode active material, binder (PVDF), conductive agent (SP), and conductive agent (CNT) are mixed evenly in NMP at a mass ratio of 96:2:1.5:0.5. Subsequently, the mixed positive electrode slurry is evenly coated on aluminum foil, dried in a vacuum oven at 100°C, and then roll-pressed to obtain a positive electrode sheet.
[0133] (2) Preparation of negative electrode sheet
[0134] The negative electrode active material (artificial graphite) is mixed with a binder (carboxymethyl cellulose, CMC) and a conductive agent (SP) in a mass ratio of 96:2.5:1.5, dispersed in deionized water, uniformly mixed and dispersed to form a negative electrode slurry, and the negative electrode slurry is uniformly coated on the negative electrode collector (copper foil), and the negative electrode collector coated with the negative electrode slurry is transferred to a vacuum environment in an oven at 100°C for drying for 12 hours, and then rolled to obtain a negative electrode sheet.
[0135] (3) Preparation of electrolyte
[0136] Ethylene carbonate (EC) and ethyl methyl carbonate (EMC) are mixed in a weight ratio of 3:7 to obtain an organic solvent, and then fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1.15 mol / L.
[0137] (4) Preparation of diaphragm
[0138] Polyethylene (PE) diaphragm is used.
[0139] (5) Preparation of batteries
[0140] The positive electrode sheet, separator and negative electrode sheet prepared above are assembled to obtain a bare cell without liquid injection; the bare cell is placed in an outer packaging foil, and the prepared electrolyte is injected into the dried bare cell, and a lithium-ion battery is obtained through vacuum packaging, standing, forming, sorting and other processes.
[0141] Examples 2 to 21 and Comparative Examples 1 to 4
[0142] Examples 2 to 21 and Comparative Examples 1 to 4 respectively provide a lithium ion battery, and the preparation method is basically the same as that of Example 1, except that:
[0143] In the preparation of the positive electrode sheet:
[0144] In step (1.1),
[0145] For preparation of LMFP:
[0146] LiMn a Fe b The values of a / b in the PO4 chemical formula are shown in Table 1-1 and Table 1-2; the amount of deionized water is adjusted to control the concentration of reactive ions to meet Table 1-1 and Table 1-2; the particle size Dn50 of LMFP meets Table 1-1 and Table 1-2;
[0147] For preparation of LFP:
[0148] The linear speed of the mixed material sand milling and the linear speed of the finished product sand milling are shown in Table 1-1 and Table 1-2; the temperature of the sintering platform is controlled as shown in Table 1-1 and Table 1-2; the particle size Dn50 of LFP meets Table 1-1 and Table 1-2;
[0149] In step (1.2), LMFP and LFP are mixed according to the mass ratios shown in Table 1-1 and Table 1-2;
[0150] In the preparation of the negative electrode sheet:
[0151] The mass ratios of the negative electrode active material, the binder and the conductive agent are adjusted as shown in Table 1-1 and Table 1-2.
[0152] Table 1-1
[0153]
[0154] Table 1-2
[0155]
[0156] U and r of each embodiment and comparative example were tested; the testing methods of the above items are as follows:
[0157] U detection method:
[0158] 1) Constant capacity: The secondary battery is left at 25°C for 120 minutes, and then discharged at a constant current of 0.33C to 2.5V; after being left at 20 minutes, it is charged at a constant current of 0.33C to 4.25V, charged at a constant voltage of 0.05C, and discharged at a constant current of 0.33C to 2.5V; after the above steps are repeated once, the charging capacity Q0 of the second cycle is obtained;
[0159] (2) Draw a charging curve: After standing at 25°C for 120 min, charge at a constant current of 2C to an upper voltage limit of 4.25 V to obtain the charging capacity Q and voltage V data;
[0160] (3) Derivative calculation is performed on the above QV data, and then dQ is divided by dV to obtain dQ / dV; dQ / dV is used as the ordinate and voltage V is used as the abscissa to obtain a dQ / dV-V curve;
[0161] (4) In the dQ / dV-V curve, the peak position of the characteristic peak with a voltage between 3.4 V and 3.6 V on the horizontal axis is the potential U1 of the first platform, and the peak position of the characteristic peak with a voltage between 3.6 V and 3.8 V on the horizontal axis is the potential U2 of the second platform; the potential difference between the first platform and the second platform is U = U2 - U1, in V.
[0162] Test method of r:
[0163] (1) The positive electrode and negative electrode in the secondary battery are disassembled and reassembled into a single battery. The separator used is a PE separator. There is no special restriction on the electrolyte composition. The injection amount is sufficient to ensure that there is free electrolyte when the battery is charged to the upper limit voltage. A copper wire is fixed on the negative electrode side as the third electrode;
[0164] (2) After the single-chip battery is assembled, it is allowed to stand at 25°C for 120 minutes, first charged to 4.25V at a constant current of 0.03C, then discharged to 2.5V at a constant current of 0.3C, then charged to 4.25V at a constant current of 0.33C, then charged to 0.05C at a constant voltage, allowed to stand at 25°C for 10 minutes, and then discharged to 2.5V at a constant current of 0.33C; after repeating twice, the third electrode is plated with lithium using the positive electrode at 0.01C for 6 hours; after the lithium plating is completed, it is charged at 0.33C to the voltage of the first platform; allowed to stand at 25°C for 30 minutes, and the EIS test is continued; the negative electrode and the third electrode are monitored; the test frequency is 0.01 ~10 6 Hz;
[0165] (3) After the test, the EIS data is obtained and the low-frequency oblique line area is taken as ω -0.5 -Z' curve of the real part of impedance, take the slope σ of the straight line in the lowest frequency region; substitute this slope into the formula: DLi + =(R 2 T 2 ) / (2A 2 n 4 F 4 C 2 σ 2 ) to get DLi + It is the lithium ion diffusion coefficient (r); where R is the gas constant J / mol / K, T is the absolute temperature of the reaction K, and A is the area of the negative electrode material immersed in the electrolyte cm 2 , n is the number of reaction electrons, F is the Faraday constant C / mol, and C is the molar concentration of lithium ions mol / cm 3 .
[0166] Figure 1 is a charging curve diagram of the lithium-ion battery of Example 12, wherein SOC (%) represents the charging capacity Q, Figure 2 dQ / dV-V curve of the lithium ion battery of Example 12.
[0167] The test results of each embodiment and comparative example are shown in Table 2.
[0168] Table 2
[0169]
[0170] The fast charge time and fast charge cycle life of lithium-ion batteries are tested as follows:
[0171] (1) Fast charging time at room temperature 8%-80% SOC:
[0172] The lithium-ion battery is discharged at a constant current of 0.05C to 2V, and then disassembled in an empty state; the disassembly environment is maintained at room temperature and low humidity; after disassembly, the positive and negative electrodes are immediately packaged in aluminum-plastic bags to isolate them from external moisture and air; the electrodes are transferred to a glove box, and after the electrolyte is evaporated, the pieces are cut and weighed, and the full battery is assembled, and the copper wire is fixed to the surface of the negative electrode; the liquid is subsequently injected, and the battery is left to stand at room temperature for 24 hours to obtain a full battery;
[0173] The above full battery was fully charged to 4.25V at 0.05C, and discharged to 2.5V at 0.33C constant current; after standing for 10 minutes, it was charged to 4.25V at 0.33C constant current, and continued to charge at constant voltage until 0.05C was cut off. After standing for 10 minutes, it was discharged to 2.5V at 0.33C constant current. Based on the last week's charging capacity as the standard, it was charged to 8% SOC at 0.33C, and charged at a constant current of 2C-1.8C-1.6C-1.4C-1.2C-1C-0.8C-0.6C-0.4C-0.3C-0.2C-0.1C-0.05C with an upper limit voltage of 4.25V and a negative electrode to lithium potential of 0mV as the cutoff conditions, until it was fully charged to 100% SOC or the current dropped to 0.05C, and the charging was cut off. The charging time of 8%-80% SOC was counted.
[0174] (2) Capacity retention rate after 100cls fast charge cycle at room temperature:
[0175] The lithium-ion battery was subjected to a charge and discharge cycle test at 25°C using a battery charge and discharge tester. The charge and discharge regime was as follows: 0.33C constant current discharge to 2.5V, standing for 10 minutes, 0.33C constant current charge to 4.25V, constant voltage charge to 0.05C cut-off, standing for 10 minutes, 0.33C constant current charge to 4.25V, and the above charge and discharge were repeated twice; the battery was charged to 4.3V at 1C constant current and constant voltage at a temperature of 25°C, and then discharged to 2.5V at 1C constant current, and the above 1C charge and 1C discharge cycles were repeated for 100 cycles. The discharge capacity of the first cycle was recorded as Q1, and the discharge capacity of the 100th cycle was recorded as Q100. The capacity retention rate of 100cls = (Q2 / Q1) × 100%.
[0176] The test results are shown in Table 3.
[0177] Table 3
[0178]
[0179] According to the test results in Table 3, the lithium-ion batteries prepared in various embodiments of the present invention have good fast charging performance, the fast charging time is ≤26.9min, and the fast charging cycle stability is good, and the capacity retention rate of the fast charging cycle of 100cls is ≥94.3%.
[0180] According to Examples 1 to 4, Examples 10 to 13, and Examples 17 to 21, it can be seen that when the potential difference between the first platform and the second platform of the lithium-ion battery and the lithium ion diffusion coefficient of the corresponding negative electrode sheet when the battery potential is in the first platform satisfy 0.125≤U×r≤0.152, the lithium-ion battery has a shorter fast charge time and a higher capacity retention rate of 100cls of fast charge cycles; when U is in the range of 0.11 to 0.19V, or r is in the range of 0.7×10 -8 ~1.25 × 10 -8 cm 2 / s, the battery's fast charging performance is better.
[0181] According to Examples 6 to 9 and Examples 14 to 16, it can be seen that when the Dn50 particle size of LFP is in the range of 90 to 200 nm, the Dn50 particle size of LMFP is in the range of 50 to 180 nm, and the mass ratio of LFP to LMFP is (1.5 to 19): 1, the lithium-ion battery can achieve comprehensive good fast charging performance.
[0182] According to Comparative Examples 1 to 4, when the U×r of the lithium-ion battery exceeds the scope of the technical solution of the present invention, even if the value of U is between 0.11 and 0.19 V and the value of r satisfies 0.7×10 -8 ~1.25 × 10 -8 cm 2 / s, the fast charging performance of lithium-ion batteries is still generally poor, the fast charging time is too long, or the fast charging retention rate is too low.
[0183] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A secondary battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, characterized in that: The positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material, and the positive electrode active material comprises a phosphate material; The secondary battery is charged at 25°C at a 2C rate in a voltage range of 2.5-4.25V to obtain a charging curve, wherein the charging curve includes three charging platforms with different potentials, which are recorded as the first platform, the second platform and the third platform in descending order of potential; The potential difference between the first platform and the second platform is recorded as U, the unit of measurement is V, and the range of U is 0.07~0.19V; When the potential of the secondary battery is at the first platform, the lithium ion diffusion coefficient of the corresponding negative electrode is r, and the unit of measurement is: ×10 -8 cm 2 / s, the range of r is 0.7×10 -8 ~1.28 × 10 -8 cm 2 / s; The secondary battery satisfies the following relationship: 0.06≤U×r≤0.
189.
2. The secondary battery according to claim 1, characterized in that: The secondary battery satisfies the following relationship: 0.124≤U×r≤0.
152.
3. The secondary battery according to claim 1, characterized in that: The range of U is 0.13~0.16V.
4. The secondary battery according to claim 1, characterized in that: The range of r is 0.9×10 -8 ~1.05×10 -8 cm 2 / s.
5. The secondary battery according to claim 1 or 2, characterized in that: The phosphate materials include lithium iron manganese phosphate and lithium iron phosphate.
6. The secondary battery according to claim 5, characterized in that: The Dn50 particle size of the lithium iron phosphate is 90-200 nm.
7. The secondary battery according to claim 5, characterized in that: The Dn50 particle size of the lithium manganese iron phosphate is 50-180 nm.
8. The secondary battery according to claim 5, characterized in that: The mass ratio of the lithium manganese iron phosphate to the lithium iron phosphate is 1.5-19:
1.
9. The secondary battery according to claim 8, characterized in that: The mass ratio of the lithium manganese iron phosphate to the lithium iron phosphate is 2-6:
1.
10. The secondary battery according to claim 1, characterized in that: The negative electrode plate includes a negative electrode current collector and a negative electrode active material layer arranged on at least one surface of the negative electrode current collector, the negative electrode active material layer contains negative electrode active materials, and the negative electrode active materials include at least one of natural graphite, artificial graphite, mesophase carbon microbeads, hard carbon, soft carbon, silicon, SiOx, silicon carbon, and lithium titanate.
11. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 1 to 10.
Citation Information
Patent Citations
Electrode active material for anion-deficient lithium transition metal phosphate compound, method of preparing same, and electrochemical device using same
CN101789507A
Lithium ion secondary battery for starting of internal combustion engine
CN105206868A